Comparison of amoxicillin and metronidazole effect on three-drug regimen for the treatment of Helicobacter pylori infection in children - Karam-Ali Kasiri; Abolfazl Khoshdel; Afshin Karimi; Morteza Sedehi; Niloufar Kasiri (Wolters Kluwer Medknow Publications, 2017)
Helicobacter pylori is an important risk factor for chronic gastritis, peptic ulcer, and gastric cancer. Three-drug regimen is the first-line treatment for this infection, but the response rate to treatment varies in different geographical regions. This study was conducted to comparatively determine the effect of amoxicillin and metronidazole on three-drug regimen to treat H. pylori infection in 1-15-year-old children. This clinical trial was conducted on 82 patients aged 1-15 years with convenience sampling referring to the Endoscopy Unit of Hajar Hospital, Shahrekord. Group 1 was administered with clarithromycin, amoxicillin, and omeprazole (CAO), and Group 2 with, clarithromycin, metronidazole, and omeprazole (CMO). One month after completion of the treatment, stool antigen test was used to study the eradication of H. pylori. Data were analyzed using SPSS software by Chi-square test. Three of the 82 patients were excluded from the study because of side effects caused by drugs. Nearly 87.2% of the patients in CAO-treated group and 92.5% in CMO-treated group had response to treatment. There was no significant difference in eradication rate between the two regimens (P = 0.43). The two regimens displayed no superiority over each other for eradicating H. pylori infection and response rate to treatment in children aged 1-15 years.